Pembinaan Peserta Didik di Madrasah Aliyah Swasta Pondok Pesantren Irsyadul ‘Ibad Batang Hari - Fadlilah; Bawaihi; Nuning Setia Ningsih (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to describe the activities of coaching students at MA Pondok Pesantren Irsyadul 'Ibad Batang Hari. This research uses a qualitative approach. The informant selection technique uses snowball sampling. Data collection is carried out through observation, interviews, and documentation. Data analysis using interactive model analysis techniques by Miles and Huberman. The results showed that student development is based on the potential and interests of students which are contained in the form of student targets (achievement plans). There are two main components that are prepared in the development of students, namely accompanying teachers who meet the requirements as teachers in madrasahs and supporting facilities provided by involving the entire madrasah environment. In providing various learning services, MA Pondok Pesantren Irsyadul 'Ibad Batang Hari positions itself as an open system, so that madrasahs always make contact with the community and the surrounding environment to get support both pre, during and after the implementation of educational programs. Coaching intracurricular activities emphasizes more on character building and instilling a maturing culture which is reflected in the lack of regulations for students.